2005
DOI: 10.1002/jcp.20501
|View full text |Cite
|
Sign up to set email alerts
|

Effect of laminin‐1 on intestinal cell differentiation involves inhibition of nuclear nucleolin

Abstract: Intestinal epithelial cells are characterized by continuous renewal and differentiation events, which may be influenced by the basement membrane, and in particular laminins, which are major components of this specialized extracellular matrix. The function and signaling pathways of laminins in these processes are still poorly documented. In this study, we investigated the possible role and the subcellular localization of nucleolin, a nuclear shuttling protein, in relation to differentiation of human intestinal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 61 publications
1
27
0
Order By: Relevance
“…Knockdown of nucleolin expression by the small interfering RNA strategy mimicked the effect of laminin-1 as it resulted in the induction of cell polarization and differentiation. It was also shown that both effects of laminin-1 on Caco-2/TC7 cells, induction of sucrase and loss of nuclear nucleolin, are mediated by a β1-integrin dependent cascade that implicates activation of the p38 MAPK pathway (Turck et al, 2006 and Figure 5). …”
Section: Regulation By Extracellular Matrix Moleculesmentioning
confidence: 94%
See 1 more Smart Citation
“…Knockdown of nucleolin expression by the small interfering RNA strategy mimicked the effect of laminin-1 as it resulted in the induction of cell polarization and differentiation. It was also shown that both effects of laminin-1 on Caco-2/TC7 cells, induction of sucrase and loss of nuclear nucleolin, are mediated by a β1-integrin dependent cascade that implicates activation of the p38 MAPK pathway (Turck et al, 2006 and Figure 5). …”
Section: Regulation By Extracellular Matrix Moleculesmentioning
confidence: 94%
“…(B) Nucleolin inhibition induces differentiation of Caco-2/TC7 cells: a small interfering RNA strategy, used to knock down nucleolin expression, leads to a clear induction of the morphological polarization of the cells (arrows point to the brush border membrane) and of sucrase as compared to control cells such as Caco-2 cells cultured on laminin-1 (not illustrated). The scheme summarizes data obtained by Turck et al (2005Turck et al ( , 2006 showing that the β1-integrin-mediated adhesion of cells to laminin-1 leads to signal transduction that implicates the p38 MAP kinase and to the modulation of differentiation gene expression via loss of nucleolin and induction of Cdx2.…”
Section: Derivation Of Various Differentiated Cell Clonesmentioning
confidence: 96%
“…Nucleolin plays essential roles in rDNA transcription, rRNA maturation, ribosome assembly and nucleocytoplasmic transport (Ginisty et al, 1999;Srivastava and Pollard, 1999). As a multifunctional protein, nucleolin has also been proposed to be a nuclear matrix-binding protein (Gotzmann et al, 1997), to interact with telomerase (Khurts et al, 2004) and to be involved in the regulation of apoptosis (Mi et al, 2003), intestinal cell differentiation (Turck et al, 2006) and remodeling of nucleosomes (Angelov et al, 2006). Although many functions of nucleolin have been clarified, previous studies have fallen short of demonstrating its functions during mitosis.…”
Section: Journal Of Cell Science 2092mentioning
confidence: 99%
“…In addition, molecules such as urokinase, which are involved in mechanisms regulating pericellular proteolysis and cellsurface adhesion mitogenesis, bind and are cointernalized along with cell-surface nucleolin (9,10). Other cell-surface nucleolin binding proteins, such as laminin-1, factor J, and L-and P-selectins, are involved in cell differentiation, cell adhesion regulation, leukocyte trafficking, inflammation, and angiogenesis (11)(12)(13)(14). Cell-surface nucleolin has been validated as a novel target for anticancer therapy by using several molecules such as endostatin, the AS1411 aptamer, acharan sulfate, the F3 tumor-homing peptide coupled to radioactive isotopes (15)(16)(17), and the HB-19 pseudopeptide (18).…”
Section: Introductionmentioning
confidence: 99%